DEINDUSTRIALIZATION AND REINDUSTRIALIZATION IN THE COURSE OF ECONOMIC TRANSFORMATION (Third Sector Social Economic Review, 2020)
From the second half of the 20th century, the process of deindustrialization has emerged firstly in developed industrial countries and then in developing countries. The decline of the relative share of the manufacturing in the economy has been accompanied by the expansion of service activities, thereby creating a new global structure where the driving force of economic growth has been the growth of the services sector. In this study, the deindustrialization phenomenon has been evaluated separately for developed countries that started to deindustrialize after completing their industrialization and for developing countries that started to deindustrialize prematurely before completing their industrialization. For developed countries; the reasons such as the effect of changes in the final demand patterns resulting from changes in income, productivity differences between the main sectors, increased outsourcing and offshoring, shifting of labor-intensive industries to developing countries and decreases in manufacturing employment due to automation of production seem to be prominent factors. In developing countries, policy transformations seem to be the main reason of deindustrialization and it is observed that the determination of financial sector has increased despite the decreasing share of the real sector in economic growth. The exit from deindustrialization process, which has a negative effect on developing economies, is through “re-industrialization”. After the 2008 financial crisis, policy preferences towards re-industrialization emerged on a global scale. With this concept, it is aimed to reinstate the manufacturing industry production as the engine of growth. According to our evaluation, the permanent solution to the long-term fundamental economic problems of Turkey and many developing economies, which seem to deteriorate further due to deindustrialization such as increasing unemployment, import-dependent manufacturing and foreign trade deficit-based growth is industrialization. In the reindustrialization concept, the development of new industries in accordance with dynamic comparative advantages and technology production are of primary importance. Reindustrialization will be sustainable to the extent that it relies on environmentally cleaner and resource-efficient production processes and seeks social inclusion. Supporting production in high-value and innovative service areas that have strong ties with industrial production in our country is also considered as a complementary factor.
Keywords: Deindustrialization; Premature Deindustrialization; Reindustrialization; Manufacturing.